Analysis of the Kuala Kapuas District Court Decision Regarding Legal Protection for Children Who Become Victims of Sexual Violence : Analisis Putusan Pengadilan Negeri Kuala Kapuas Terkait Perlindungan Hukum Bagi Anak yang Menjadi Korban Kekerasan Seksual - Yuniar Imroatus Solikhah; Emy Rosnawati (Academia Open, 2020)
In Law No. 35 year 2014 about child protection, explained that each child is potential, and the young generation of the nation's successors. The country has a strategic role, so it is obligatory to protect the child from all forms of inhumane treatment that can lead to violations of human rights. One form of human rights violations is sexual violence. This research uses normative research methods with a legal approach as well as a case approach. To analyze whether the fundamental difference of the two judges in the District Court of Kuala Kapuas criminal matter number 164/Pid.Sus/2019/PN. Klk with the participation of the State of Kupang criminal Matters No. 249/Pid. Sus/2019/PN.KPG in the decision to take the case of a criminal lawsuit in child sexual violence. The occurrence of the decision of judge or disparity of judges is not separated from the discretion of the judges and also due to the minimum sanction system and maximum sanctions in the Indonesian criminal system. The consideration of the Tribunal judges gave a 14-year criminal verdict against the defendant Armayansyah, considering that the defendant was a lecturer or teacher in the victim's school and the age of the victim who still stepped on 13 years.